Moderating effect of heritage spatial proximity on the relationship between perceptual proximity and residents' attitudes towards tourism. Issue 3 (3rd July 2019) - Lwoga, Noel Biseko
ABSTRACT: This study examines the moderating effect of residents' spatial proximity to heritage on the relationship between their perceptual proximity to heritage and tourism attitudes. Questionnaire surveys were conducted with residents living around Kaole Ruins site in Tanzania. The results indicate that perceptual proximity relates positively and significantly to attitude. The positive relationship was more significant to individuals living far from the site than to individuals living close to the site. Residents living close to site are prone to land ownership problems emanating from heritage management. Integrating spatial and perceptual dimensions of heritage provides a better understanding of tourism attitudes.